Penggunaan Bahasa dalam Forum Adat Martahi Godang Masyarakat Batak Angkola: Kajian Sosiolinguistik - Risky Pratama siregar; Immanuel Bintang Cristopher Batubara; Asriaty r Purba; Dani Maichel Gultom; Hod Burju Pakpahan (Jurnal Pendidikan Bahasa, 2026)
This study examines the linguistic practices in the Martahi Godang traditional forum of the Batak Angkola community using a qualitative-descriptive method through observation, interviews, and documentation. The research addresses four main questions: the position of Martahi Godang as a cultural domain, patterns of code-switching, the relationship between kinship structure and language use, and the strategies of politeness and traditional metaphors. The study employs Fishman’s theory of language domains and language maintenance, along with sociolinguistic concepts of code-switching, politeness, and ritual language. The findings reveal that Martahi Godang functions as a discursive space that sustains the Angkola language through hierarchical, metaphor-rich, and symbolically grounded forms of speech. Code-switching between Angkola and Indonesian occurs for clarification and emphasis, while Angkola remains dominant in ritual segments and the delivery of moral messages. The kinship structure of mora–kahanggi–anak boru strongly shapes speaking rights, lexical choices, and politeness strategies. The consistent use of Angkola within the forum fulfills Fishman’s four indicators of language maintenance: stable domain, intergenerational transmission, symbolic prestige, and ritual function. Thus, Martahi Godang serves as a key institution in preserving the vitality of the Angkola language and cultural identity